Silent embolism after stent-assisted coiling of cerebral aneurysms: diffusion-weighted MRI study of 75 cases. (8th August 2013) - Hahnemann, M L; Ringelstein, A; Sandalcioglu, I E; Goericke, S; Moenninghoff, C; Wanke, I; Forsting, M; Sure, U; Schlamann, M
Abstract : Purpose: New ischemic brain lesions are common findings after cerebral diagnostic angiography and endovascular therapy. Diffusion-weighted MRI (DWI) can be used for detection of these lesions. The aim of the present study was to investigate the incidence of DWI lesions after stent-assisted coiling and the evaluation of possible risk factors. Methods: The study included a total of 75 consecutive patients treated with stent-assisted coiling. Post-procedural DWI of the brain was performed to detect ischemic lesions. Demographic data, aneurysm characteristics and angiographic parameters were correlated with properties of DWI lesions. Results: In post-procedural DWI, 48 of the 75 patients (64%) had 163 DWI lesions in a pattern consistent with embolic events. The number of patients with DWI lesions was significantly increased in older patients (≥55 years) and longer intervention times (≥120 min). The ischemic brain volume was significantly increased in older patients (≥55 years) as well as in patients who were implanted with a shorter stent (<20 mm). Conclusions: Thromboembolic events are common after stent-assisted coiling with an incidence comparable to DWI studies after coiling alone. Despite several devices and low operator experience, stent-assisted coiling for intracranial aneurysms has a very low risk of permanent neurologic disability. Further studies are necessary to improve the safety of stent-assisted coiling for patients in conditions with increased risk potential (age, procedure time, stent length).